A comparison of concurrent programming and cooperative multithreading under load balancing applications - Maris, Justin T.; Keen, Aaron W.; Ishihara, Takashi; Olsson, Ronald A. (Concurrency and computation, 2004)
Two models of thread execution are the general concurrent programming execution model (CP) and the cooperative multithreading execution model (CM). CP provides nondeterministic thread execution where context switches occur arbitrarily. CM provides threads that execute one at a time until they explicitly choose to yield the processor. This paper focuses on a classic application to reveal the advantages and disadvantages of load balancing during thread execution under CP and CM styles; results from a second classic application were similar. These applications are programmed in two different languages (SR and Dynamic C) on different hardware (standard PCs and embedded system controllers). An SR‐like run‐time system, DesCaRTeS, was developed to provide interprocess communication for the Dynamic C implementations. This paper compares load balancing and non‐load balancing implementations; it also compares CP and CM style implementations. The results show that in cases of very high or very low workloads, load balancing slightly hindered performance; and in cases of moderate workload, both SR and Dynamic C implementations of load balancing generally performed well. Further, for these applications, CM style programs outperform CP style programs in some cases, but the opposite occurs in some other cases. This paper also discusses qualitative tradeoffs between CM style programming and CP style programming for these applications. Copyright © 2004 John Wiley & Sons, Ltd.